2013
DOI: 10.1039/c2nr33512c
|View full text |Cite
|
Sign up to set email alerts
|

Improving the dispersity of detonation nanodiamond: differential scanning calorimetry as a new method of controlling the aggregation state of nanodiamond powders

Abstract: Detonation nanodiamond (ND) is a suitable source material to produce unique samples consisting of almost uniform diamond nanocrystals (d = 3-5 nm). Such samples exist in the form of long stable aqueous dispersions with narrow size distribution of diamond particles. The material is finding ever increasing application in biomedicine. The major problem in producing monodispersed diamond colloids lies in the necessity of deagglomeration of detonation soot and/or removing of clusters formed by already isolated core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 23 publications
7
70
0
Order By: Relevance
“…Forming of aggregates or the formation of a protein layer on the diamond can increase the distance between the NV center and the target molecule. It has to be noted that our study is different from well-known aggregation in detonation nanodiamonds [15, 16]. These aggregate during synthesis without the presence of other molecules.…”
Section: Introductionmentioning
confidence: 62%
“…Forming of aggregates or the formation of a protein layer on the diamond can increase the distance between the NV center and the target molecule. It has to be noted that our study is different from well-known aggregation in detonation nanodiamonds [15, 16]. These aggregate during synthesis without the presence of other molecules.…”
Section: Introductionmentioning
confidence: 62%
“…Even so, it was possible to conclude that C-O (287.0 eV) 37, 38 is the main bond in the composite (as expected due to the known carbon sp 3 hybridization in diamonds), followed by C-C/C-H (285.0 eV) and C=O (288.9 eV), 37, 38 while other type of chemical bonds cannot be confirmed by this characterization technique. These results are in agreement with TPD analysis, 12 were phenol or ether (C-OH, C-O-C; 286.3 eV 36 ) and quinone (C=O) groups were detected, while carboxylic acids (-COOH), carboxylic anhydrides (-C(O)2O) and lactones (-COO) were not identified in the composite.Several authors39,40 have reported that detonated NDs when dispersed in liquid medium induce strong particle aggregation, attributing the phenomenon to the harsh conditions in the detonation chamber that leads to the creation of dandling bonds on the ND surface. The free electron surfaces can cooperate via intermolecular surface forces such as van der Waals and hydrogen bonding creating covalent bonds between the primary particles 39.…”
mentioning
confidence: 99%
“…24,25 In conclusion, we propose a physically consistent way of interpreting Raman spectra of nanoparticles. Since the 3D dispersion function takes into account the anisotropy of the phonon dispersion, the model built in this way has a straightforward physical meaning.…”
mentioning
confidence: 99%